2000
DOI: 10.1007/s001920050010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Reporting Pelvic Floor Defects: the Revised New York Classification System

Abstract: The authors have devised a conceptual model and reporting system for characterizing, grading and staging pelvic floor defects. The system is user friendly and simple to learn and apply. It is based on commonly known anatomic landmarks and can be performed without memorizing or referring to a separate characterization and reporting plan. Completing the accompanying forms is self-explanatory and provides the information needed for proper comprehension and recording of anatomic defects. The model and reporting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The standardization of terminology for female pelvic organ prolapse (POPQ system) has allowed evaluation of uterovaginal prolapse by a standard system relative to clearly defined points [6]. However, it does not identify the specific defects in the lateral vaginal walls and nor does it determine parameters for successful repair [9,10]. An ICS and AUGS survey showed that the acceptance rate for POPQ was low with 40 % of practitioners routinely using the system and 33.5% of the members never using it [11].…”
Section: Discussionmentioning
confidence: 99%
“…The standardization of terminology for female pelvic organ prolapse (POPQ system) has allowed evaluation of uterovaginal prolapse by a standard system relative to clearly defined points [6]. However, it does not identify the specific defects in the lateral vaginal walls and nor does it determine parameters for successful repair [9,10]. An ICS and AUGS survey showed that the acceptance rate for POPQ was low with 40 % of practitioners routinely using the system and 33.5% of the members never using it [11].…”
Section: Discussionmentioning
confidence: 99%
“…All patients had a focused urogynecologic history, a pelvic defect evaluation using the Revised New York Classification System [9], pelvic defect staging using the International Continence Society criteria [10], Q-tip [11], and catheterized post-void residual determinations, urinalysis with culture, and multichannel urodynamic testing and/or office cystoscopy, as indicated. Additionally, filling provocative cystometry, and urethral pressure profilometry with the prolapse extended and reduced were also obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria for this study were symptomatic anterior vaginal wall prolapse with preoperative presence of urinary retention [5] defined as PVR ‡100 cc, the absence of any neurological disorders and ability to use and retain a pessary without difficulty. All patients underwent a detailed urogynecologic history and physical examination including urethral axis determination by cotton swab (Q tip), site-specific prolapse grading by the International Continence Society (POPQ) [6] and New York Classification (NYC) [7] Systems, spontaneous uroflowmetry, PVR urine determination, urine analysis and urine culture. All studied patients with elevated PVR ( ‡100 ml) had repeated PVR determinations and confirmation of abnormally elevated residual volume at each voiding trial along with complex uroflowmetry.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of surgery a suprapubic catheter was placed in all patients and was discontinued when voiding resumed spontaneously and the PVR was <100 cc. At 3 months following surgery, all patients underwent a detailed sitespecific evaluation in the supine position during maximal Valsalva and empty bladder using the site-specific prolapse grading proposed by the International Continence Society (POPQ) [6] and New York Classification (NYC) [7] Systems, along with Q-tip testing, uroflowmetry and PVR measurement. Cure of urinary retention was defined as a PVR <100 cc at 3 months postoperatively.…”
Section: Methodsmentioning
confidence: 99%